Strategi Pengembangan Lembaga Keuangan Mikro Mendukung Pengentasan Kemiskinan Di Perdesaan - Yopi Saleh; Yayat Hidayat (Universitas Wahid Hasyim, 2011)
Poverty in rural areas is a central issue of national mitigation which can’t be postponed and should be a priority in the implementation of social welfare development. Lack of access to capital sources, markets and technologies, as well as farmer’s organizations are still weak to be one of our problem. Optimizing the potential of existing financial institutions could be an alternative source of funding for farmers and rural communities, namely the development of MFIs. To that end, this paper aims to identify the problems of MFIs, to analyzes the potential of MFI’s which can use as basis for the future development strategy and key success factors of empowerment MFI. From the discussion, MFIs development can be the one of effective solution in reducing poverty with the help of the role and intervention of various parties, both governmental, non-governmental and community. This can seen from the success of the empowerment of MFIs that have been implemented in Bangladesh, Philipine and China. Keywords: MFI, Poverty, Rural.